BIMBINGAN KONSELING MELALUI KOMUNIKASI EMPATIK BERDASARKAN NILAI-NILAI ISLAM - Ihda A’yunil Khotimah (STPI Bina Insan Mulia Yogyakarta, 2020)
Children are the mandate of God who is born by bringing each other's nature, parents have an obligation to provide the best education for their growth and development and educators are the second parents in the school who will support by stimulating various potential children. The process of growth and development of children sometimes experiences obstacles to achieving the ability of minimum indicators in the school curriculum. Barriers experienced at an early age can be a problem for future child development. The situation that needs to be understood by parents and educators is to equate perceptions of children's problems so that they get guidance and counseling as needed. Problems faced by early childhood usually consist of physical-motoric, intellectual, social, moral, emotional and spiritual problems. The different perceptions of child problems are caused by the behavior, attitudes and abilities that children display when they are at home different from when they are at school. To strengthen the argument about children's problems, parents and educators sometimes have difficulty communicating. Parents do not accept child shortages, while educators face their own problems in school. To get a collective agreement requires effective communication between educators and parents of students. As taught in Islam that to invite to the goodness and truth of a Muslim needs to speak well, not to deteriorate or to find fault with others. Islamic values ​​such as life goals, life tests, the advantages and disadvantages of every human being that has been studied, will be able to strengthen educators and parents in helping to solve children's problems so that they are ready to continue to a higher level.